The Sacred Flesh: On Camus’s Philosophy of the Body - Mryglod, Camilla (My University, 2010)
The focus of my thesis concerns what I refer to as Camus’s ‘philosophy of the body.’ This study in part addresses the scholarly debate about how his texts are related. Camus himself says of certain writers that their “books form a whole, ‘in which each is to be understood in relation to the others, and in which they are all interdependent.’” ' If this understanding of authorship equally applies to Camus’s works, the question concerns linkage. What underlies this wholeness? Broadly speaking, there are three approaches to understanding the relation between his texts: thematic, philosophic, and existential. None of these ways is truly independent of the other. Each emphasizes a different aspect of Camus’s project. He is an artist, thinker and man. Once again we are returned to the question of linkage. The thematic approach tends to absolutize one mood or insight, though Camus cautions against this. The philosophical approach generally reads the texts dialectically. But Camus’s interest is in our living experience, not in a flight of the intellect. An existential approach, understood correctly, concerns not a theory of but a meditation on our concrete existence. If Camus’s works are read together as a sustained meditation on existence, the integrity of the artist, thinker and man is preserved. Each facet - beauty, truth and life - is held in a working tension as opposed to absolutizing or subsuming any one aspect. Still the question remains. What underlies this integrity? Quite literally, the body. I argue that Camus’s life work evokes a new way of seeing, thinking and speaking about the body. In this dissertation, then, I look at various ways in which the body is manifested across a selection of his essays and novels. I also consider what might be some ofthe implications ofsuch manifestations.
Keywords: Albert Camus; Le Mythe de Sisyphe; L’Étranger; La Peste; L'Homme révolté; philosophy of the body